Creating a Learning Culture for Medical Consortia in China. Issue 1 (January 2018) - He, Guozhong; Chen, Zimin
Abstract : In China's recent health care reforms, both individuals and organizations have shown an ever-growing desire and demand for new knowledge and skills. A health care delivery system (HCDS) should explore new ways for creating a learning organization (LO) and should organically combine HCDS culture construction with the LO construction to build a cultural atmosphere that is conducive to the development of the LO. This article describes the implementation phase, characteristics, and realization strategy of an HCDS construction for the ultimate purpose of enhancing HCDS cohesion, solidarity, and sustainable development.